Histopathological Correlation of Cases with Epithelial Cell Abnormality Detected in Cervicovaginal Smear Screenings of Turkish Women and Their Association with HPV Subtypes - Kılıç HÖ; İlhan Çelik Ö (International Journal of General Medicine)
Hilal Özlem Kılıç,1,* Özgür İlhan Çelik2,* 1Department of Pathology, Muğla Training and Research Hospital, Muğla, Turkey; 2Department of Pathology, Muğla Sıtkı Koçman University, Faculty of Medicine, Muğla, Turkey*These authors contributed equally to this workCorrespondence: Özgür İlhan Çelik, Muğla Sıtkı Koçman University, Faculty of Medicine, Department of Pathology, Muğla, 48000, Turkey, Tel +905063058343, Email oilhancelik@gmail.com; ozgurilhancelik@mu.edu.trBackground: Cervical cancer is the second most common gynecological malignancy worldwide and one of the leading cause of cancer-related mortality among women. In Turkey, its incidence remains considerably high. Early detection through Pap (Papanicolaou) smear and HPV (Human Papilloma virus) DNA testing plays a vital role in reducing morbidity and mortality.Objective: This study aims to evaluate the diagnostic concordance between cytological screening methods and definitive histopathological diagnoses, and to identify factors associated with diagnostic discrepancies.Methods: A retrospective analysis was conducted on 643 cases that received both cytological and histopathological diagnoses. Patient data, including age, HPV-DNA type, presence of endocervical cells, atrophy, and inflammation, were reviewed and compared.Results: Of the SCC (squamous cell carcinoma) cases, 96.2% were found in the 30– 65 age group HPV positivity and the presence of endocervical cells decreased with age. SCC was three times more frequent in HPV 16/18-positive cases than in other genotypes. A statistically significant inverse relationship was observed between increasing age and diagnostic concordance. HPV negativity was significantly associated with diagnostic discordance, while HPV genotype had no significant effect. Therefore, it would be appropriate to perform HPV screening at regular intervals. So our findings suggest that diagnostic concordance between cytology and histology is influenced by age and HPV status. Since HPV 16/18 positivity significantly increases the risk of SCC, screening strategies should take both age and genotype into consideration. High concordance between cytological screening results and histological diagnosis is very important for the prevention of advanced stage SCC.Keywords: cervix, cervicovaginal smear, epithelial cell abnormality, HPV